Remember September: Re-performing the Burmese 'Saffron Revolution' at the Singapore Biennale1. Issue 1 (11th February 2016) - EISNER, RIVKA SYD
Abstract : In the autumn of 2008, artists Chaw Ei Thein and Richard Streitmatter-Tran and collaborators laboured outside in the sweltering heat to create September Sweetness, an installation made of five and a half tons of sugar, for the second Singapore Biennale. September Sweetness was intended to honour the memory of those who perished in the 2007 uprisings known as the 'Saffron Revolution' in Myanmar, and to show the 'erosion of hope' for a better future. September Sweetness took place a number of years ago now, but the intentionally ephemeral nature of the art object itself – a sugar temple that gradually melted away – as well as its social reception, multiple meanings and collaborative construction process, and the ways in which the memory of the work continue to resonate with past and present politics, make the performative acts that radiated through this project important to recount.